The occurrence of Ixodes ricinus ticks and important tick-borne pathogens in areas with high tick-borne encephalitis prevalence in different altitudinal levels of the Czech Republic Part I. Ixodes ricinus ticks and tick-borne encephalitis virus - Daniel, M; Danielová, V; Kříž, B; Růžek, D; Fialová, A; Malý, M; Materna, J; Pejčoch, M; Erhart, J (Epidemiologie, mikrobiologie, imunologie, 2016)
STUDY OBJECTIVE: The aim of the three-year study (2011-2013) was to monitor population density of Ixodes ricinus ticks and its infection rate with the tick-borne encephalitis virus in areas with a high incidence of tick-borne encephalitis as reported in the previous decade 2001-2010. Such a comprehensive and long-term study based on existing epidemiolo-gical findings has not previously been conducted in Europe. MATERIAL AND METHODS: In the areas of the Ústí nad Labem Region, Olomouc Region, South Bohemian Region, and Highlands Region, 600 m2 plots were selected in the local optimal I. ricinus habitats where tick flagging was performed every year in the spring-summer and autumn seasons of the questing activity. In total, 18,721 I. ricinus ticks (1448 females, 1425 males, and 15,848 nymphs) were collected and investigated. RESULTS AND CONCLUSION: The results have shown that the differences in the infection rate of I. ricinus observed between regions are driven by variation in the density of the local I. ricinus populations which is influenced by the characteris-tics of the whole local biocenosis. The overall prevalence estimate of TBE virus in Ixodes ricinus ticks at the altitudes below 600 m a.s.l. was 0.096 % (95% CI 0.055-0.156) for nymphs, and 0.477 % (95% CI 0.272-0.773) for adults. The dynamics of the seasonal variation in I. ricinus populations, depending primarily on the climatic factors, are behind the interyear differences in the infection rate of ticks and, consequently, in the epidemiological situation of tick-borne encephalitis. The nymph to adult ratio was 5.5 on average but showed great interregional variability (from 10.3 in the Ústí nad Labem Region to 1.8 in the Highlands Region). It might be used in the future as one of the indicators of the composition of the local I. ricinus population and of the level of the circulation of tick-borne pathogens in zoonotic sphere and also for use in the health risk assessment in a given area. Despite the permanent expansion of ticks and tick-borne pathogens in higher altitudes the high risk limit for human infection with tick-borne encephalitis is 600 m a.s.l. in the Czech Republic.
Keywords: Prevalence; Česká republika; Ixodes; Encephalitis, Tick-Borne; Czech Republic; viry klíšťové encefalitidy; prevalence; Male; klíště; Animals; Encephalitis Viruses, Tick-Borne; Female; mužské pohlaví; ženské pohlaví; Ixodes ricinus - tick-borne encephalitis virus - occurrence - altitude - region - season.; zvířata; klíšťová encefalitida